Nanoscale Faceting and Ligand Shell Structure Dominate the Self‐Assembly of Nonpolar Nanoparticles into Superlattices. Issue 20 (17th April 2022) - Bo, Arixin; Liu, Yawei; Kuttich, Björn; Kraus, Tobias; Widmer‐Cooper, Asaph; de Jonge, Niels
Abstract: Self‐assembly of nanoscale structures at liquid–solid interfaces occurs in a broad range of industrial processes and is found in various phenomena in nature. Conventional theory assumes spherical particles and homogeneous surfaces, but that model is oversimplified, and nanoscale in situ observations are needed for a more complete understanding. Liquid‐phase scanning transmission electron microscopy (LP‐STEM) is used to examine the interactions that direct the self‐assembly of superlattices formed by gold nanoparticles (AuNPs) in nonpolar liquids. Varying the molecular coating of the substrate modulates short‐range attraction and leads to switching between a range of different geometric structures, including hexagonal close‐packed ( hcp ), simple hexagonal ( sh ), dodecahedral quasi‐crystal ( dqc ), and body‐centered cubic ( bcc ) lattices, as well as random distributions. Langevin dynamics simulations explain the experimental results in terms of the interplay between nanoparticle faceting, ligand shell structure, and substrate–NP interactions. Abstract : Superlattice formation by self‐assembly in liquid is a nanoengineering technique with broad technological applications. Liquid‐phase electron microscopy reveals that faceted nanoparticles assemble differently on SiN surfaces with altered electrostatic and long‐range attraction, demonstrating that the nanoscale morphology of the nanoparticles and the substrate's surface control the self‐assembled superlattices.